L’aiuto a morire nell’ordinamento spagnolo e definizione del contesto eutanasico (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay analyzes Spain’s recent organic legislation on state assisted dying. After analyzing the context in which the reform has developed, this articles seeks to identify the strengths and weaknesses of the new law. Moreover, the article considers the compliance of the new law with the Spanish Constitution and the European Convention on Human Rights. Finally, the analysis focuses on the legislative vacuum following the Italian Constitutional Court’s ruling no.242/2019.
Keywords: Spanish organic law; help to die; assisted suicide; euthanasia; conscientious objection